Multiple Hotspot Mutations Scanning by Single Droplet Digital PCR. (1st February 2018) - Decraene, Charles; Silveira, Amanda B; Bidard, François-Clément; Vallée, Audrey; Michel, Marc; Melaabi, Samia; Vincent-Salomon, Anne; Saliou, Adrien; Houy, Alexandre; Milder, Maud; Lantz, Olivier; Ychou, Marc; et al.
Abstract: BACKGROUND: Progress in the liquid biopsy field, combined with the development of droplet digital PCR (ddPCR), has enabled noninvasive monitoring of mutations with high detection accuracy. However, current assays detect a restricted number of mutations per reaction. ddPCR is a recognized method for detecting alterations previously characterized in tumor tissues, but its use as a discovery tool when the mutation is unknown a priori remains limited. METHODS: We established 2 ddPCR assays detecting all genomic alterations within KRAS exon 2 and EGFR exon 19 mutation hotspots, which are of clinical importance in colorectal and lung cancer, with use of a unique pair of TaqMan ® oligoprobes. The KRAS assay scanned for the 7 most common mutations in codons 12/13 but also all other mutations found in that region. The EGFR assay screened for all in-frame deletions of exon 19, which are frequent EGFR-activating events. RESULTS: The KRAS and EGFR assays were highly specific and both reached a limit of detection of <0.1% in mutant allele frequency. We further validated their performance on multiple plasma and formalin-fixed and paraffin-embedded tumor samples harboring a panel of different KRAS or EGFR mutations. CONCLUSIONS: This method presents the advantage of detecting a higher number of mutations with single-reaction ddPCRs while consuming a minimum of patient sample. This is particularly useful in the context of liquid biopsy because the amount of circulating tumor DNA is often low. This method should be useful as a discovery tool when the tumor tissue is unavailable or to monitor disease during therapy.